Evaluating the results of Nocturnal Penile Tumescence test utilizing Iranian erection analyzer - a case control study - Alinejad Khorram, Amir; Allameh, Farzad; Kolahchi, Roya; Khoshnamak, Ali (Archives of Men's Health, 2024)
Background: Erectile dysfunction (ED) is a male sexual condition that affects 10% to 25% of men globally. Identifying the underlying cause of ED in males is a critical aspect of diagnosis. For many years, the Rigiscan® devices have been utilized to distinguish between psychological and physiological erectile dysfunction. The purpose of this study was to look at the validity of an Iranian erection analyzer equipment for evaluating nocturnal penile tumescence (NPT) in ED patients referred to Shahada-e-Tajrish Hospital in 2021. Materials and Methods: Patients who were diagnosed with vascular erectile dysfunction by doppler ultrasound evaluation and intra-cavernosal injection (ICI) test were included in this study. Also, a group of sexually healthy volunteers were included in the study as a control group. After receiving written informed consent, both groups were evaluated for two nights with the NPT test with the Iranian Erection Analyzer device. The results of the two groups were collected and analyzed. Results: A total of 45 patients with erectile dysfunction and 29 sexually healthy individuals were included in the study. Both groups were hospitalized for two nights in the isolation room of the urology ward and the NPT test was performed for them. Our results showed that the NPT test performed by the Iranian Erection Analyzer device with 62% sensitivity and 100% specificity is capable of distinguishing patients with erectile dysfunction from sexually healthy men. Conclusions: Based on our results, the Iranian Erection Analyzer device is accurate enough to diagnose patients with erectile dysfunction and can be used in clinics.